Banded microstructures in rapidly solidified Al-3 wt% Er. (April 2020) - Gianoglio, Dario; Marola, Silvia; Battezzati, Livio; Aversa, Alberta; Bosio, Federico; Lombardi, Mariangela; Manfredi, Diego; Lorusso, Massimo
Abstract: Banded and discontinuous eutectic microstructures were found in melt quenched ribbons and laser melted single tracks of an Al-3%wt Er alloy, respectively. The bands occurring in ribbons are made of alternate primary α-Al phase and eutectic. Their formation is well described by the Han-Trivedi model for banding in alloy solidification. Microstructure fluctuations between fibrous and discontinuous eutectic are seen in laser melted single tracks on the same length scale of bands due to change in local temperature gradient. Overall, various transitions in phase morphology are found in thin zones of material constituting a valuable guideline for interpretation of the solidification mechanism. Nano-indentation tests show that the fine microstructures induce substantial hardening. Graphical abstract: Image 1 Highlights: Fine banded microstructure discovered in melt spun Al-3%wt Er. Fibrous and uncoupled refined eutectics occur in laser single tracks of Al-3%wt Er. Strong dispersion hardening discovered by nano-indentation experiments.